Higher niacin intakes improve the lean meat rate of Ningxiang pigs by regulating lipid metabolism and gut microbiota - Wang, Zhaobin; Zeng, Xianglin; Zhang, Cheng; Wang, Qianqian; Zhang, Weidong; Xie, Junyan; Chen, Jiashun; Hu, Qin; Wang, Qiye; Yang, Huansheng; Yin, Yulong (Frontiers in Nutrition, 2022)
As one of the local pig breeds in China with a high fat rate, improving the lean meat rate of Ningxiang pigs through nutritional intervention is an urgent issue to be solved. As an important feed additive, niacin plays an important role in lipid metabolism. The purpose of this study was to investigate the regulation and mechanism of niacin on fat deposition in Ningxiang pigs. Thirty-four Ningxiang pigs (53.34 ± 2.78 kg) were randomly divided into two groups with five replicates each, with three to four Ningxiang pigs per replicate. The control group was fed a basal diet (contained 22 mg/kg niacin), and the experimental group was fed the same diet supplemented with an additional 100 mg/kg of niacin. The experimental period lasted 60 days. One Ningxiang pig was selected for slaughter sampling for each replicate. This study found that the lean meat percentage of Ningxiang pigs in the experimental group was significantly increased (P < 0.05), accompanied by a significant decrease in fat percentage (P < 0.05). 16S rRNA sequencing analysis found an abundance of Streptococcus in experimental group (P < 0.05), along with significantly decreased levels of Lactobacillus (P < 0.05). The changes in some OTUs belonging to Firmicutes, Bacteroidota and Actinobacteriota were closely related to the changes of fat rate and lean meat rate of Ningxiang pigs (P < 0.05). LC-MS metabolomics analysis found that about 43.75% of the differential metabolites were related to lipids and lipid-like molecules in the liver (P < 0.05). Spearman correlation analysis showed correlations among the carcass traits, microbiota and liver metabolites. In conclusion, niacin improves lean meat percentage and reduces fat deposition by regulating lipid metabolism and gut microbiota composition in Ningxiang pigs.